A Cacophony of Signals: Woodpecker Sexbots, Squirrel NORAD, and Other Robotic Systems. (1st June 2019) - Ingram, Ian
This article discusses the author's robotic artworks, which consider the human-made body's future as a willful entity and the nature of communication. The robots use computer vision or sound signal processing to search the world for the signals of target species and then attempt to respond through similar gestural and audible signalling. The robots are trying to communicate with the animals and, in part, allow human communion with those animals in ways that human bodies and umwelts don't allow. That human narrative stamps itself heavily onto the projects is confirmed by these becoming things like a hermaphroditic sexbot for Pileated Woodpeckers and a NORAD equivalent for Grey Squirrels.